ANALISIS PENGARUH KEPEMIMPINAN TRANSAKSIONAL, MOTIVASI, DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN - GOEYANTO, FEBRIAN (Universitas Katolik Widya Mandala Surabaya, 2012)
The high competition in bussines makes companies continue to increase performance in order to stay competitive. The purpose of this study to determine whether transactional leadership, motivation, and organizational commitment affect job satisfaction and employee performance. This study used a sample of 120 people. Data analysis technique used is SEM (Structural Equation Modelin). From the results obtained it is evident that the leadership, motivation, and organizational commitment affect job satisfaction and performance and job satisfaction also affects job performance.